Engineering Limonene and Bisabolene Production in Wild Type and a Glycogen-Deficient Mutant of Synechococcus sp. PCC 7002 - Davies, Fiona K.; Work, Victoria H.; Beliaev, Alexander S.; Posewitz, Matthew C. (Frontiers in Bioengineering and Biotechnology, 2014)
The plant terpenoids limonene (C10H16) and α-bisabolene (C15H24) are hydrocarbon precursors to a range of industrially-relevant chemicals. High-titer microbial synthesis of limonene and α-bisabolene could pave the way for advances in in vivo engineering of tailor-made hydrocarbons, and production at commercial scale. We have engineered the fast-growing unicellular euryhaline cyanobacterium Synechococcus sp. PCC 7002 to produce yields of 4 mg L-1 limonene and 0.6 mg L-1 α-bisabolene through heterologous expression of the Mentha spicata L-limonene synthase or the Abies grandis (E)-α-bisabolene synthase genes, respectively. Titers were significantly higher when a dodecane overlay was applied during culturing, suggesting either that dodecane traps large quantities of volatile limonene and α-bisabolene that would otherwise be lost to evaporation, and/or that continuous product removal in dodecane alleviates product feedback inhibition to promote higher rates of synthesis. We also investigate limonene and bisabolene production in the ΔglgC genetic background, where carbon partitioning is redirected at the expense of glycogen biosynthesis. The Synechococcus sp. PCC 7002 ΔglgC mutant excreted a suite of overflow metabolites (α-ketoisocaproate, pyruvate, α-ketoglutarate, succinate and acetate) during nitrogen deprivation, and also at the onset of stationary growth in nutrient-replete media. None of the excreted metabolites, however, appeared to be effectively utilized for terpenoid metabolism. Interestingly, we observed a 1.6 to 2.5-fold increase in the extracellular concentration of most excreted organic acids when the ΔglgC mutant was conferred with the ability to produce limonene. Overall, Synechococcus sp. PCC 7002 provides a highly promising platform for terpenoid biosynthetic and metabolic engineering efforts.